Crystallization of Covalent Organic Frameworks for Gas Storage Applications - Lijuan Zhu; Yue-Biao Zhang (Molecules, 2017)
Covalent organic frameworks (COFs) have emerged as a new class of crystalline porous materials prepared by integrating organic molecular building blocks into predetermined network structures entirely through strong covalent bonds. The consequently encountered “crystallization problem” has been conquered by dynamic covalent chemistry in syntheses and reticular chemistry in materials design. In this contribution, we have reviewed the progress in the crystallization of COF materials and their hydrogen, methane and carbon dioxide gas storage properties for clean energy applications.